Assessing the Effectiveness of Rice Farming Corps Insurance in Protecting Farmers and Ensuring Legal Certainly - Elisatris Gultom (KRTHA BHAYANGKARA, 2024)
Indonesia is an agricultural country because most of the Indonesian population works in the farm sector, including rice farming. Ironically, rice farming has not developed much and has become a mainstay for the Indonesian people even though this business has long been known and cultivated by most Indonesians living in rural areas. The factor of disasters due to climate change, especially in Java Sumatra, Sulawesi, and parts of Kalimantan, is often the reason why farmers are reluctant to farm so the agricultural sector has not developed much. This research aims to determine the validity of Rice Farming Business Insurance (AUTP) from the aspect of national insurance law and the effectiveness of AUTP as a means of protection for farmers This research is normative juridical research that focuses on secondary data analysis, which comes from primary, secondary and tertiary legal materials related to AUTP, while the data collection technique used is literature study or document study. The research typology used is analytical descriptive, namely describing fully and comprehensively the application of AUTP as a means of protecting rice farmers from the potential for crop failure to be further analyzed so that solutions can be found to existing problems. The research conclusion shows that juridically AUTP meets all the requirements for the existence of an insurance agreement so that AUTP is valid and has legal certainty even though AUTP is not specifically regulated in the Commercial Code; AUTP has not been effectively used as a means of protecting rice farmers because it still faces internal obstacles originating from the farmers themselves and externally. In order for AUTP to be effective in providing protection for farmers in Indonesia, it is necessary to carry out increasingly massive outreach to AUTP and optimize the use of technological facilities.